A facile one-pot solvothermal synthesis of CoFe2O4/RGO and its excellent catalytic activity on thermal decomposition of ammonium perchlorate. Issue 87 (5th September 2016) - Chen, Teng; Du, Ping; Jiang, Wei; Liu, Jie; Hao, Gazi; Gao, Han; Xiao, Lei; Ke, Xiang; Zhao, Fengqi; Xuan, Chunlei
Abstract : A novel catalyst CoFe2 O4 /RGO has been synthesized and shows enhanced catalytic activity on thermal decomposition of ammonium perchlorate. Abstract : CoFe2 O4 /RGO hybrids have been successfully fabricated via a facile one-pot solvothermal method, which were characterized by X-ray diffraction (XRD), Raman, Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS). During this process, graphene oxide was reduced to graphene (RGO) and CoFe2 O4 nanoparticles were deposited on the RGO. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that the average size of CoFe2 O4 /RGO hybrids was 120 nm, which was smaller than that of bare CoFe2 O4, implying that RGO could effectively prevent CoFe2 O4 nanoparticles from aggregating. To investigate the catalytic activity of the as-synthesized CoFe2 O4 particles and CoFe2 O4 /RGO hybrids, the thermal decomposition of ammonium perchlorate (AP) was characterized by differential thermal analyser (DTA). Both of the two exothermic processes were merged into a sole exothermic process with the addition of bare CoFe2 O4 and CoFe2 O4 /RGO hybrids, though there was no change in the position of the phase transition temperature of AP. Moreover, the catalytic activity of CoFe2 O4 /RGO hybrids is higher than that of bare CoFe2 O4, due to the large surface area and enhanced properties of RGO in the hybrids. The temperature programmed reduction (TPR) measurements showed that the reduction temperature of CoFe2 O4 /RGO decreased by 55 °C compared with bare CoFe2 O4, which further confirmed the higher catalytic activity of CoFe2 O4 /RGO of than that of CoFe2 O4 nanocomposites. Hence, CoFe2 O4 /RGO hybrids could be a promising additive in modifying the burning behaviour of AP-based composite propellant.